Improvement of biocomposite performance under low-velocity impact test - a review - Sanivada, Usha Kiran Kumar (2021)
2nd World Conference on Advanced Materials for Defense, AUXDEFENSE 2020Virtual, Online6 July 2020 through 7 July 2020Code 266239